Lithium metatitanate enhanced solid–solid reaction in a lithium–nitrogen–hydrogen system. Issue 24 (15th March 2015) - Zhang, Tengfei; Isobe, Shigehito; Wang, Yongming; Hashimoto, Naoyuki; Ohnuki, Somei
<x xml:space="preserve">Abstract</x> In the Li–N–H system, an end temperature of under 260 °C was achieved, and the lowest peak temperature occurred at 223 °C.